Incidencia del juego en el desarrollo psicomotriz de los estudiantes del segundo año de educación básica de la escuela Agustín Albán del barrio Guapulo, cantón Pujilí, durante el período lectivo 2013 – 2014 - Acurio Benavides, Jenny Mariela (2015)
The present investigation was conducted with the purpose of having a teaching tool to help children / as, since the game is a basic element in the development of the child / a, and is a fun resource necessary for development. That is why play is important for learning and holistic development of children as they learn about life playing. Furthermore parent activities which allow proper development of training in children, while it would guide them to carry it right over and have the tools to help them cope with problems a adapt to them evolves. Through play children seek, explore, test and discover the world for themselves, as an effective tool for education. Under this play helps them to psychomotor improvement skills and the development of gross and fine motor; also sensory and mental development: through discrimination of shapes, sizes, colors, textures, etc. Finally affective capabilities experienced in emotions like surprise, excitement or joy; and as a solution to meet their emotional conflicts needs and desires in real life may not be helping them face everyday situations.